Prevalence of Batrachochytrium dendrobatidis, B. salamandrivorans, and Ranavirus in the US domestic pet amphibian trade - Viadanna, Pedro H. de O.; Brinkman, Ashley; Vimont, Ben; Gray, Matthew J.; Warwick, Alexa R.; Poudyal, Neelam C.; Pearhill, Robert A. I.; Brunner, Jesse L. (Frontiers in Amphibian and Reptile Science, 2025)
The global trade of live animals facilitates the spread of emerging pathogens, such as the deadly amphibian pathogens, Batrachochytrium dendrobatidis (Bd), B. salamandrivorans (Bsal), and Ranavirus spp (Rv). Yet little is known about their prevalence within domestic trade networks. We used an anonymous surveillance scheme to estimate the prevalence of Bd, Bsal, and Rv within and among businesses in the US domestic pet amphibian trade. We found that Bd was rare within affected businesses, but common among businesses, whereas Rv was common within affected businesses, but rare among them. However, the aggregate prevalence of both pathogens was very low: Bd prevalence was 1.9% and Rv was 2.9% among enclosures. Bsal was not detected in this or prior surveys among pet owners and is most likely absent. The rarity (or absence) of pathogens in the US domestic pet amphibian trade, in contrast to their relative pervasiveness at US borders, may be due in part to biosecurity practices common in the industry. Half of participants quarantined newly acquired animals and most used gloves. How practices and operation of the domestic pet amphibian trade magnify or, as our study suggests, reduce the risk of pathogen persistence or spread requires further study.